2022
DOI: 10.1167/tvst.11.9.2
|View full text |Cite
|
Sign up to set email alerts
|

Topical Ripasudil for the Treatment of Primary Corneal Endothelial Degeneration in Dogs

Abstract: Purpose The purpose of this study was to evaluate the tolerability and efficacy of topical rho-kinase inhibitor ripasudil in the treatment of primary corneal endothelial degeneration (PCED) in dogs. Methods Twenty-one eyes of 12 client-owned, PCED-affected dogs received topical ripasudil 4 times daily. Ophthalmic examination, ultrasonic pachymetry (USP), Fourier-domain optical coherence tomography (FD-OCT), and in vivo confocal microscopy were performed at baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…This premise is further supported by our recent study demonstrated that ripasudil administration for 1 year in dogs with primary corneal endothelial degeneration improved or stabilized disease in 62% of patients ( Fig. 27 ) ( Michalak et al, 2022 ). In aggregate, there is a pressing need to study how ROCK inhibitors modulate ECM deposition and remodeling in corneal endothelial cells from FECD patients in vitro as well as in relevant animal models and clinical trials.…”
Section: Corneal Endotheliumsupporting
confidence: 54%
See 2 more Smart Citations
“…This premise is further supported by our recent study demonstrated that ripasudil administration for 1 year in dogs with primary corneal endothelial degeneration improved or stabilized disease in 62% of patients ( Fig. 27 ) ( Michalak et al, 2022 ). In aggregate, there is a pressing need to study how ROCK inhibitors modulate ECM deposition and remodeling in corneal endothelial cells from FECD patients in vitro as well as in relevant animal models and clinical trials.…”
Section: Corneal Endotheliumsupporting
confidence: 54%
“…Further characterization of this condition in three at-risk breeds, Boston Terriers, German Shorthaired and Wirehaired Pointers, revealed reduced ECD, endothelial polymegathism and pleomorphism, progressive corneal edema with increased thickness, a thickened DM-endothelial complex and guttae-like lesions ( Shull et al, 2018 ; Thomasy et al, 2016a ). The model has been utilized to investigate a novel surgical procedure ( Horikawa et al, 2016 ) and the ROCK inhibitor ripasudil ( Michalak et al, 2022 ) over a 1-year period since CED progresses more quickly in canine patients than FECD does in humans. In aggregate, the striking similarities between FECD and CED combined with the similar environments that dogs and humans reside in suggest that successful therapies for CED may be more likely to translate successfully to FECD patients than those tested solely in healthy animal models with induced corneal endothelial injury.…”
Section: Corneal Endotheliummentioning
confidence: 99%
See 1 more Smart Citation